Crashproof codes [flight software]. - Hess, R.K.
Boeing Co. and NASA have joined forces for the Active Aeroelastic Wing (AAW) Project to test the way a modified F/A-18 strike fighter uses its wings. The AAW was designed to be flexible enough to be twisted on demand in flight and it could herald nothing less than a revolution in aviation. The twisting can be used to control the plane's roll, reducing and ultimately eliminating the need for ailerons and flaps and their associated hardware. AAW-equipped planes would result to increased fuel efficiency and improved maneuverability, able to execute sharper turns at higher speeds. A special flight software was developed to keep track of the plane's speed, altitude, and attitude while monitoring the pilot's controls for commands. Based on a set of rules known as control laws, the software must then translate any commands from the pilot into movements of the aircraft's various control surfaces such as the rudders or, most significantly, the flaps that flex the AAWs. Despite its complex and critical job, the flight software is compact, consisting of only about 13,000 lines of source code written in the Ada language.
Keywords: Active Aerolastic Wing project; Aviation; Flight software; Supersonic aircraft